2011
DOI: 10.1007/s00125-011-2400-5
|View full text |Cite
|
Sign up to set email alerts
|

Multivesicular exocytosis in rat pancreatic beta cells

Abstract: Aims/hypothesisTo establish the occurrence, modulation and functional significance of compound exocytosis in insulin-secreting beta cells.MethodsExocytosis was monitored in rat beta cells by electrophysiological, biochemical and optical methods. The functional assays were complemented by three-dimensional reconstruction of confocal imaging, transmission and block face scanning electron microscopy to obtain ultrastructural evidence of compound exocytosis.ResultsCompound exocytosis contributed marginally (<5% of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
39
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(45 citation statements)
references
References 47 publications
5
39
1
Order By: Relevance
“…More frequently, fused chain of insulin granules were observed in the primary beta cells ( Fig. 2A, arrow), similar to previous reports (Kwan and Gaisano, 2005;Hoppa et al, 2012). They collapse into the plasma membrane and release insulin in a multiple-granular manner ( Fig.…”
Section: Flash Photolysis and Depolarization Can Elicit Clathrinindepsupporting
confidence: 90%
See 1 more Smart Citation
“…More frequently, fused chain of insulin granules were observed in the primary beta cells ( Fig. 2A, arrow), similar to previous reports (Kwan and Gaisano, 2005;Hoppa et al, 2012). They collapse into the plasma membrane and release insulin in a multiple-granular manner ( Fig.…”
Section: Flash Photolysis and Depolarization Can Elicit Clathrinindepsupporting
confidence: 90%
“…However, compound exocytosis of prefused insulin granules was reported in rat pancreatic beta cells in 2005 (Kwan and Gaisano, 2005). Recently, compound exocytosis has been further demonstrated to play a important role under conditions associated with the global elevation of cytosolic Ca 2+ (Hoppa et al, 2012), which is the condition that augments the bulk-like endocytosis found in the present study. Our electron microscope data also show examples of compound fusion of several granules to the plasma membrane (Fig.…”
Section: Disscusionsupporting
confidence: 49%
“…3). Sequential SG-SG fusion and compound exocytosis have been studied in recent years, in various cell types, with multi-photon imaging [30,31] and other imaging modalities [9]. Realising that static EM images could not distinguish these exocytotic events, we employed TIRFM to rigorously and quantitatively assess the spatio-temporal dynamics of these two types of SG-SG fusion: sequential SG-SG fusion and true compound fusion.…”
Section: Syn-3 Is a T-snare On Sgsmentioning
confidence: 99%
“…Third, fluorescence intensity between inner and outer red circles (corresponding to grey lines in the bottom graphs) depicting dissipation of SG cargo release is also much larger in the massive SG fusion than that in single SG fusion. We thus considered that these massive fusion events represent genuine compound fusion of several SGs that were already prefused before a lead SG underwent exocytotic fusion with the PM [8,9,28]. Two additional examples of compound exocytosis (left We then examined whether loss of function (siRNA knockdown) or gain of function (genetic overexpression) of SYN-3 could influence these SG-SG fusion events in INS-1 cells.…”
Section: Syn-3 Is a T-snare On Sgsmentioning
confidence: 99%
See 1 more Smart Citation